2019
DOI: 10.1002/ppp3.25
|View full text |Cite
|
Sign up to set email alerts
|

Succulent plant diversity as natural capital

Abstract: Societal Impact Statement Drought‐tolerant plants are increasingly recognized as a resource to mitigate the consequences of climate change. Succulent plants use stored water to sustain metabolism during regular droughts; succulence is a highly successful adaptation that has evolved in thousands of species throughout the plant kingdom. Desert (xeromorphic) succulent species are a potentially relevant resource to manage environments and energy supply in the hottest and driest places. However, many species are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 89 publications
0
47
0
2
Order By: Relevance
“…Agave (Asparagaceae) and Opuntia (Cactaceae) species can operate at near‐maximum productivity with low water requirements (Borland et al, 2011; Borland, Griffiths, Hartwell, & Smith, 2009) and exhibit lower greenhouse gas emissions and nitrogen leaching than maize (Davis et al, 2012). Opuntia ficus‐indica and Euphorbia tirucalli (Euphorbiaceae) have also been considered potential bioenergy crops and been determined to produce promising yields with low rainfall (Mason et al, 2015) but require careful consideration of the potentially negative ecological impact of introducing invasive species outside their natural range (Grace, 2019). In a global scale GIS‐based productivity model, simulations for the year 2070 on low‐grade land suggested that Opuntia ficus‐indica alone has the capacity to meet extreme bioenergy scenarios (>600EJ yr −1 ) and is highly resilient.…”
Section: Challenges and Risks Of Getting From Plant To Powermentioning
confidence: 99%
See 1 more Smart Citation
“…Agave (Asparagaceae) and Opuntia (Cactaceae) species can operate at near‐maximum productivity with low water requirements (Borland et al, 2011; Borland, Griffiths, Hartwell, & Smith, 2009) and exhibit lower greenhouse gas emissions and nitrogen leaching than maize (Davis et al, 2012). Opuntia ficus‐indica and Euphorbia tirucalli (Euphorbiaceae) have also been considered potential bioenergy crops and been determined to produce promising yields with low rainfall (Mason et al, 2015) but require careful consideration of the potentially negative ecological impact of introducing invasive species outside their natural range (Grace, 2019). In a global scale GIS‐based productivity model, simulations for the year 2070 on low‐grade land suggested that Opuntia ficus‐indica alone has the capacity to meet extreme bioenergy scenarios (>600EJ yr −1 ) and is highly resilient.…”
Section: Challenges and Risks Of Getting From Plant To Powermentioning
confidence: 99%
“…However, this approach has limitations when the aim is to identify candidate species that may be morphologically dissimilar to relatives known to possess a trait of interest (e.g., domesticated crops and their wild relatives), if the trait has not been systematically characterized in a plant group, and if highly novel candidate species are sought. In those cases, candidate species can be predictively identified from the clades in the tree of life in which that trait is most likely to occur (Ernst et al., 2016; Grace, 2019; Rønsted, Savolainen, Mølgaard, & Jäger, 2008; Zhu et al, 2011). Machine learning analysis, recently successful in the search of new antibiotics (Stokes et al, 2020), could help to separate the search for candidate species from their classification or tree of life altogether, facilitated by curated trait datasets (Kattge et al, 2020).…”
Section: Discovering New Energy Sources From Plantsmentioning
confidence: 99%
“…In desert environments, plants must be able to cope with all three factors (Moore, Vicré‐Gibouin, Farrant, & Driouich, ). The ability to store and use water in a regulated manner is a remarkable and crucial adaptation in the ecological success of succulent plants (Grace, ), which are estimated to include ca . 12,000 species in diverse lineages of the angiosperm tree of life (Moore et al, ; Nyffeler & Eggli, ).…”
Section: Introductionmentioning
confidence: 99%
“…Today, desert plants, especially CAM succulents, are receiving renewed interest as resilient crops and natural capital under climate change (Davis et al., 2019; Grace, 2019; Owen, Fahey, & Griffiths, 2016; Stewart, 2015). Compared to conventional C 3 and C 4 crops, CAM plants require tenfold less water per unit dry biomass produced (Mason et al., 2015).…”
Section: Discussionmentioning
confidence: 99%